Cortical abnormalities associated with pediatric and adult Obsessive-Compulsive Disorder: Findings from the Enigma Obsessive-Compulsive Disorder Working Group - Boedhoe, P; Schmaal, L; Arnold, P; Benedetti, F; Beucke, J; Cheng, Y; Denys, D; Fitzgerald, K; Gruner, P; Hoexter, M; Huyser, C; James, A; et al. (Elsevier, 2017)
Brain imaging studies on structural abnormalities in OCD have been inconsistent, partially due to limited statistical power, clinical heterogeneity, and methodological differences. Here, we present data of the largest study to date on cortical brain measures in OCD patients and healthy controls by using meta- and mega-analyses.